Grebennikovius, a new genus to accommodate Epactoides basilewskyi (Balthasar, 1960) (Coleoptera: Scarabaeidae: Deltochilini) - Mlambo, Sukoluhle; Scholtz, Clarke H.; Deschodt, Christian M. (Zootaxa, 2019)
Phacosoma basilewskyi Balthasar, 1960 was described for a peculiar East African deltochiline dung beetle species. Years later, Paulian (1975) erected the deltochiline genus Madaphacosoma Paulian, 1975 for two new Malagasy species, namely Madaphacosoma humberti Paulian, 1975, as the type species, and M. betschi Paulian, 1975. Phacosoma basilewskyi was transferred to Madaphacosoma in that same publication. Later, Paulian (1991) added Madaphacosoma major Paulian, 1991 to the genus for a total of three Madagascan and one mainland African species. Recently, Madaphacosoma together with three other genera occurring in Madagascar, namely Aleiantus Olsoufieff, 1947, Phacosomoides Martinez & Pereira, 1959 and Sikorantus Paulian, 1976, were synonymized with Epactoides Olsoufieff, 1947 by Wirta & Montreuil (2008). Although Madaphacosoma basilewskyi (Balthasar, 1960) is not specifically mentioned as a new combination with three other species, M. major, M. humberti and M. betschi, catalogued on pages 661–662 in Wirta & Montreuil (2008), and the genus is treated as valid by Tarasov & Dimitrov (2016) and Tarasov (2017), it is currently lumped with the other Malagasy species in the genus Epactoides. The current accepted name for the species is thus Epactoides basilewskyi (Balthasar, 1960).